Novel β-Cyclodextrin-Based Heptavalent Glycyrrhetinic Acid Conjugates: Synthesis, Characterization, and Anti-Influenza Activity - Liang, Shuobin; Ma, Xinyuan; Li, Man; Yi, Yanliang; Gao, Qianqian; Zhang, Yongmin; Zhang, Lihe; Zhou, Demin; Xiao, Sulong (Frontiers in Chemistry, 2022)
In our continuing efforts toward the design of novel pentacyclic triterpene derivatives as potential anti-influenza virus entry inhibitors, a series of homogeneous heptavalent glycyrrhetinic acid derivatives based on β-cyclodextrin scaffold were designed and synthesized by click chemistry. The structure was unambiguously characterized by NMR, IR, and MALDI-TOF-MS measurements. Seven conjugates showed sufficient inhibitory activity against influenza virus infection based on the cytopathic effect reduction assay with IC50 values in the micromolar range. The interactions of conjugate 37, the most potent compound (IC50 = 2.86 μM, CC50 > 100 μM), with the influenza virus were investigated using the hemagglutination inhibition assay. Moreover, the surface plasmon resonance assay further confirmed that compound 37 bound to the influenza HA protein specifically with a dissociation constant of 5.15 × 10−7 M. Our results suggest the promising role of β-cyclodextrin as a scaffold for preparing a variety of multivalent compounds as influenza entry inhibitors.